2003
DOI: 10.1096/fj.03-0359fje
|View full text |Cite
|
Sign up to set email alerts
|

The presence of nitrite during UVA irradiation protects from apoptosis

Abstract: Nitrite occurs ubiquitously in biological fluids such as blood and sweat, representing an oxidation product of nitric oxide. Nitrite has been associated with a variety of adverse effects such as mutagenicity, carcinogenesis, and toxicity. In contrast, here we demonstrate that the presence of nitrite, but not nitrate, during irradiation of endothelial cells in culture exerts a potent and concentration-dependent protection against UVA-induced apoptotic cell death. Protection is half-maximal at a concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…In the present study, 10 mM nitrite showed a trend of cell accumulation in the G 0 /G 1 phase, as was observed previously at low sodium nitrite concentrations (up to 6.25 mM), whereas higher concentrations reduced the cell proliferation in the human gastric adenocarcinoma epithelial cell line (Sun et al, 2006). In another study on endothelial cells, the presence of nitrite (10 mM), but not nitrate, during UV irradiation of cells exerted a potent and concentration-dependent protection against apoptotic cell death, because of the photodecomposition of nitrite to generate NO (Suschek et al, 2003). BrdU incorporation confirmed the nitrite-mediated increase in S phase.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the present study, 10 mM nitrite showed a trend of cell accumulation in the G 0 /G 1 phase, as was observed previously at low sodium nitrite concentrations (up to 6.25 mM), whereas higher concentrations reduced the cell proliferation in the human gastric adenocarcinoma epithelial cell line (Sun et al, 2006). In another study on endothelial cells, the presence of nitrite (10 mM), but not nitrate, during UV irradiation of cells exerted a potent and concentration-dependent protection against apoptotic cell death, because of the photodecomposition of nitrite to generate NO (Suschek et al, 2003). BrdU incorporation confirmed the nitrite-mediated increase in S phase.…”
Section: Discussionsupporting
confidence: 78%
“…Nitrite therapy significantly augmented vascular density in the ischemic limbs by inducing endothelial cell proliferation and angiogenesis (Kumar et al, 2008); however, underlying mechanisms were not investigated. Nitrite also prevented endothelial cell apoptosis after UV exposure (Suschek et al, 2003). Oral administration of sodium nitrite (25-100 mg/kg) reduced lymphocytes, but augmented circulating neutrophils in BALB/c mice (Abuharfeil et al, 2001).…”
Section: Introductionmentioning
confidence: 89%
“…In our study, nitrite but not the mitochondrial-targeted antioxidant Mito-TEMPO influenced TNF-α/CHX-induced decrease in cell viability of MODE-K cells. The concentration of nitrite (10 mM) used was shown to provide complete rescue of UVA-induced apoptotic cell death in rat aortic endothelial cells [61]. We also found that nitrite reduced TNF-α/CHX-induced caspase-3/7 activation.…”
Section: Influence Of Antioxidant Related Products On Tnf-α/chx-inducsupporting
confidence: 51%
“…For example, the content of nitrite in sweat, covering skin, could provide benefit, because there is generation of NO from nitrite under UVA radiation (153). NO is a signaling molecule involved in UVB-induced melanogenesis (134).…”
Section: Discussionmentioning
confidence: 99%